Kritik Terhadap Belanda Dalam Perspektif Surat Kabar Merdeka (1945-1947) - Rafli Rafli Maulana; Tubagus Umar Syarif Hadi Wibowo; Yuni Maryuni (LPPM Institut Nasional Laa Roiba Bogor, 2023)
This thesis discusses the criticism of the Netherlands in the perspective of the Merdeka newspaper (1945-1947). This study aims to explain the important role of the press in responding to social and political conditions during the Indonesian revolution from 1945 to 1947. The method used in this research is the historical method, including: heuristics (data collection), source criticism, interpretation, and historiography. The results showed that the press media as a forum that provided information in the form of positive information to the public after the arrival of NICA and the Allies to Indonesia. Merdeka newspaper took an active role as a free newspaper without the interests of any group and pro to the Republic. It is the nationalization of a newspaper previously called Asia Raya, published in Jakarta during the Japanese period. The visualization of news and opinions became a form of criticism of the Merdeka newspaper which gave a cynical impression, expressed the cruelty of the Dutch as the main enemy, anti-Dutch imperialism, and inflamed the spirit of the people to defend the independence of the Republic of Indonesia. Until July 20, 1947 the newspaper led by B.M Diah was no longer published because its editorial headquarters was at the State Printing Press, Central Salemba, Jakarta, which was occupied by the Dutch during the First Military Aggression. Keywords: Press, Criticism, Independent Newspaper.